Phase variation in pneumococcal opacity: relationship between colonial morphology and nasopharyngeal colonization. - Weiser, J N (1994)
When colonies of encapsulated isolates of Streptococcus pneumoniae are viewed with oblique, transmitted light on a transparent surface, they are heterogeneous in appearance because of variation in opacity. There is spontaneous phase variation among at least three discernible phenotypes at frequencies from 10(-3) to 10(-6). The ability to detect differences in opacity varies according to serotype, but variation is independent of capsule expression. Electron microscopy shows no difference in chain length but suggests that autolysis occurs earlier in the growth of the transparent variant. There was no identifiable difference in membrane protein profiles of opaque and transparent variants of the same strain. In an infant rat model of nasopharyngeal carriage, there was no significant colonization by opaque variants. Efficient and stable colonization by the transparent variants was observed, suggesting a selective advantage for this phenotype in the nasopharynx. In contrast, there was no difference in the incidence of bacteremia or in the 50% lethal dose among the variants following their intraperitoneal inoculation. These results suggest that phase variation which is marked by differences in colonial morphology may provide insight into the interaction of the pneumococcus with its host.